The impact of foreign ownership on the performance of Romanian liste manufacturing companies - Iuliana Oana Mihai; Cosmin Mihai (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
The main objective of this paper is to investigate the relation between the foreign ownership and manufacturing firm performance. The study was conducted for the companies listed on Bucharest Stock Exchange, in both segments regulated and non-regulated. The final sample included 261 companies. Return on Assets (ROA), Return on Equity (ROE) and Return on Sales (ROS) were used for measuring the economic and financial performance of the firms. The foreign ownership was measured by the percentage of shares held by foreign investors. Econometric tools like linear regression analysis were used for the analysis. The results of the study suggest that there is a non-significant link between economic and financial performance and the existence of foreign ownership.
Keywords: 650; foreign capital; manufacturing; ownership; performance